Synergetic effect of bioslurry and charcoal co – composted fertilizers on soil properties and tomato (Solanum lycopersicum) productivity - Girmaw Mulugeta; Ermias Alayu; Yitayal Addis Alemayehu (PLoS ONE, 2026)
Tomato ( Solanum lycopersicum ) is one of the most widely cultivated and economically important vegetable crops worldwide, contributing significantly to food security. However, its low productivity remains a substantial concern in Ethiopia due to mainly poor soil quality and limited use of inorganic fertilizers. On the contrary, improper disposal of recyclable charcoal and anaerobic cow dung bioslurry (ACDB) wastes poses environmental pollution challenges. Hence, this study aimed to evaluate the synergetic effects of ACDB and charcoal co-composted fertilizers (ACDBCFs) on tomato productivity and soil properties. A pot experiment consisting of eight treatments (T1 - T8) was arranged in a randomized complete block design with three replications. Characterization of the five formulated ACDBCFs revealed good physico-chemical properties of pH, organic carbon, ammonium, nitrate, and orthophosphate, fluctuated from 8.9 to 9.63, 26.8 to 65.6%, 2.5 to 4.6 mgL ⁻ 1 , 11.9 to 18.2 mgL ⁻ 1 , and 0.74 to 3.1 mgL ⁻ 1 , respectively. Significant differences (p < 0.05) were observed in tomato fruit yield with relatively higher values of 2.87 and 2.73 kgpot ⁻ 1 for T6 and T8 under ACDB + charcoal (+10%) and inorganic fertilizers amendments, respectively. Principal component analysis (PCA) demonstrated strong associations between nutrient availability and tomato growth and yield component parameters. Heat map visualization further confirmed that ACDBCFs application improved soil background nutrient and carbon contents. Overall, the findings from this short-term study indicate that ACDBCFs can enhance tomato productivity while improving soil organic matter and nutrient availability. However, further long-term studies on field level validation in real soil conditions and nutrient dynamics are recommended to support large-scale adoption of this resource-recovery approach, contributing to sustainable agriculture, environmental protection, and socio-economic development.